The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1891/jnm-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

Using the Delphi Method to Validate Indicators of Respectful Maternity Care for High Resource Countries

Abstract: Background and PurposeConsistent measurement of respectful maternity care (RMC) is lacking. This Delphi study assessed consensus about indicators of RMC.MethodsA multidisciplinary panel assessed items (n = 201) drawn from global literature. Over two rounds, the panel rated importance, relevance, and clarity, and ranked priority within 17 domains including communication, autonomy, support, stigma, discrimination, and mistreatment. Qualitative feedback supported the analysis.ResultsIn Round One, 191 indicators e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…We began by adapting the wording of survey items from the Giving Voice to Mothers (GVTM) survey 15 and the subsequent version applied to Canada, the Research Examining the Stories of Pregnancy and Childbearing in Canada Today (RESPCCT) survey 24 to resonate with LGBTQ2S+ individuals who may be in monogamous, polyamorous, and multiple co‐parent family structures. Items retained from the previous instruments assess sociodemographic, clinical, and experiential factors across 12 domains of respectful care 25 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We began by adapting the wording of survey items from the Giving Voice to Mothers (GVTM) survey 15 and the subsequent version applied to Canada, the Research Examining the Stories of Pregnancy and Childbearing in Canada Today (RESPCCT) survey 24 to resonate with LGBTQ2S+ individuals who may be in monogamous, polyamorous, and multiple co‐parent family structures. Items retained from the previous instruments assess sociodemographic, clinical, and experiential factors across 12 domains of respectful care 25 …”
Section: Methodsmentioning
confidence: 99%
“…Items retained from the previous instruments assess sociodemographic, clinical, and experiential factors across 12 domains of respectful care. 25 The Community Steering Council applied theoretical and practical understandings of LGBTQ2S+ pregnancy experiences to ensure all appropriate constructs and domains were included. For example, based on feedback from the Community Steering Council, the Birth Includes Us survey was expanded to consider or include the following: (a) extended time frame, including all pregnancy experiences within a 10-year period; (b) expansive view on family building process, including diverse conception modalities like assisted reproduction; (c) multiplicity of pregnancy roles a person may experience, as a pregnant person, as partner/co-parent to a pregnant person, or as an intended parent using surrogacy; (d) expansive pregnancy experiences, including live birth, stillbirth, miscarriage, abortion; and (e) intersectional framing, to better capture the multifaceted impact of racism and other forms of oppression on gendered experiences of pregnancy care for LGBTQ2S+ people of color.…”
Section: Item Generation and Survey Constructionmentioning
confidence: 99%
“…This domain acknowledges that childbearing people from equity-deserving groups (e.g., racialized and Indigenous peoples) routinely encounter racism and discrimination in health care [ 45 , 46 ]. Racism and discrimination are embedded in organizational structures of health care in many Western contexts, resulting in inequities in maternal and infant morbidity and mortality among certain population groups [ 41 , 47 , 48 ]. Moreover, socioeconomic disparities often compound racial inequities [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a mixed methods approach provided critical insights and new understandings that would not have been identified if the study relied solely on quantitative data. Qualitative data invites diverse perspectives and expertise to be shared to bring richer insights and support a collaborative process where panel participants can more meaningfully inform the model or framework generated [41,42]. The utility of collecting both qualitative and quantitative data in Delphi studies has been noted by others who have observed that a mixed methods approach is essential for identifying framework deficiencies and necessary modifications [41][42][43].…”
Section: Plos Onementioning
confidence: 99%
“…The recommendations by World Health Organization (WHO) in 2018 emphasized the quality of interaction between women and their healthcare providers and considered good interactions as a prerequisite for positive outcomes of childbirth. 14 , 15 Additionally, respecting parturient women’s rights is one of the important aspects of medical care in which midwives, as the core of midwifery care, play the role of a spiritual and emotional catalyst to promote the capabilities and self-confidence of parturient women. Creating an effective relationship with the parturient women increases their self-confidence.…”
Section: Introductionmentioning
confidence: 99%